Penatalaksanaan Alopecia Areata (Treatment of Allopecia Areata) - Agatha Anindhita Ayu Ardhaninggar; Rahmadewi Rahmadewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2018)
Background: Alopecia Areata (AA) is a disease characterized by loss of hair from the scalp of a sudden. The main principle of treatment of AA that inhibit or alter the immunological response by modulating the inflammatory process that occurs around hair follicles. There are several options in the treatment of AA Purpose: provide insight into a variety of existing AA management. Review: AA is a form of autoimmune disease mediated by T lymphocytes that attack hair follicles and hair loss is characterized by chronic and recurrent. Based on the latest research results, the onset and severity of AA are determined by the interaction between genetic factors and environmental factors of the originator. Currently the hypothesis of AA focuses on the collapse of immune privilege status of a hair follicle and presentation of self-antigens that cause active lymphocytes. Several factors such as genetics, autoantigen, immune cell activity, and stress factors played a role in the pathogenesis of AA. The basic principle of treatment of AA, can be divided into two, namely Immunosuppressant and immunomodulatory will manipulate the inflammatory process intrakutan. Conclusion: Several therapeutic options in the AA include the injection of corticosteroids, minoxidil, immunotherapies, photochemotherapy, calcineurin inhibitors, metrotrexate, sulfasalazzine, azatioprine, laser therapy, PRP therapy, and therapy with stem cellsKey word: allopecia areata, treatment